The use of reflection-card by elite youth basketball players, head coach and team manager: effects on players' performance and perceptions of users. Issue 3 (4th May 2017) - Koh, Koon Teck; Chew, Mei Ling Evon; Kokkonen, Marja; Chew, Wai Cheong Eugene
Abstract: The purpose of the present paper was to test the effectiveness of the r-cards in sport performance, and to examine what kind of benefits and challenges the head coach, team manager and female basketball players ( N = 12) faced when using the r-cards. Mixed methods were employed to gather specific data to answer the research questions. Inferential statistical analyses were conducted to examine whether players' performances in terms of their targeted defensive rebound percentage and free-throw percentage differed across the five matches played. No significant differences were found. However, evidence from the qualitative data provides a contrasting but insightful perspective. Subjectively, the r-cards strategy was seen as beneficial because it improved the team's performance and preparations, helped the players in goal setting, identification of weaknesses, and recognition of effort. In contrast, realistic goal setting, irrelevance of some reflection questions, effort recognition, and feedback to head coach were found challenging in r-cards usage. The paper closes with a critical discussion on the implications for future use of r-cards in the field of sport coaching.